Model Teologi Gereja di Abad XXI: Studi Arah Pengembangan menuju Globalisasi - Harianto GP (Excelsis Deo: Jurnal Teologi, Misiologi, dan Pendidikan, 2019)
The model (shape, style, paradigm or style) is the most important part of seeing a development, especially the theological church. Theology here is not only interpreted as "knowledge (cognitive) about God" but also changes in the affective and psychomotor of the church towards the knowledge of God. The Church is responsible for laying the cognitive foundation of God and making changes within himself and having the skills to worship and carry out His will. In this context the term "Church Theological Model" appears. The author conducts research based on models of church theology which began from the time of the fathers of the Church to the Church of the XX century. From there it can then be arranged in the direction of development towards globalization which reaches in the direction of the models of Church theology in the Indonesian Churches. Model (bentuk, corak, paradigm atau gaya) merupakan bagian terpenting dalam melihat sebuah perkembangan, khususnya gereja berteologi.  Teologi  di sini bukan saja diartikan sebagai “pengetahuan (kognitif) tentang Tuhan” tetapi juga perubahan afektif  dan psikomotoris gereja terhadap pengetahuan akan Tuhan tersebut. Gereja bertanggungjawab untuk meletakan dasar kognitif akan Tuhan dan melakukan perubahan di dalam diri serta mempunyai keterampilan menyembah dan melaksanakan kehendak-Nya. Dalam konteks ini muncul istilah “Model Teologi Gereja”.  Penulis melakukan penelitian berdasarkan model-model teologi gereja yang dimulai sejak masa bapa-bapa Gereja hingga Gereja masa abad XX. Dari situ kemudian bisa tersusun arah pengembangan menuju globalisasi yang mencapai pada hasil arah model-model teologi Gereja di Gereja-gereja Indonesia.